2022
DOI: 10.55942/jebl.v2i2.152
|View full text |Cite
|
Sign up to set email alerts
|

The influence of work morale, work discipline, and work environment on employee performance

Abstract: This study aims to determine the effect of work morale, work discipline, and work environment on employee performance. This research method is quantitative. The source of data in this study is primary data. The primary data used is by distributing questionnaires to the respondents consisting of questions for which answer choices have been provided using a Likert scale. Likert scale with a scale range of 1-5. The population used in this study were employees of PT SAI, the sampling technique used in this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Organizational culture influences employee engagement directly and it is important for the organization's success (Bhagwandeen, 2021). The definition of a work environment is "a work condition that provides a comfortable atmosphere and working situation for employees to achieve the goals desired by the company" (Anggraini, 2024). The factors of working conditions involve the physical environment surroundings of the workplace and facilities whether they are comfortable or poor conditions.…”
Section: Working Conditionsmentioning
confidence: 99%
“…Organizational culture influences employee engagement directly and it is important for the organization's success (Bhagwandeen, 2021). The definition of a work environment is "a work condition that provides a comfortable atmosphere and working situation for employees to achieve the goals desired by the company" (Anggraini, 2024). The factors of working conditions involve the physical environment surroundings of the workplace and facilities whether they are comfortable or poor conditions.…”
Section: Working Conditionsmentioning
confidence: 99%
“…Some research showed that discipline has a positive and significant effect on employee performance. (Fajar et al, 2022;Hidayat et al, 2022;Nangoy et al, 2020;Setianingsih et al, 2023;Sitopu et al, 2021;Suwandi & Setiawan, 2022).Work discipline is needed to produce good performance also with discipline, employees will try to do the work as much as possible, resulting in better performance. Discipline must be enforced in an organization or company because, without good employee discipline, it is difficult for companies to realize their goals.…”
Section: Disciplinementioning
confidence: 99%
“…Work discipline is a crucial aspect of any job, as it ensures that employees are performing their tasks in an organized and efficient manner. It involves adhering to company policies and procedures, maintaining a positive work ethic, and respecting colleagues and superiors (Suwandi, 2019). The level of work discipline within an organization can have a significant impact on employees' decisions to continue working there (Suwandi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It involves adhering to company policies and procedures, maintaining a positive work ethic, and respecting colleagues and superiors (Suwandi, 2019). The level of work discipline within an organization can have a significant impact on employees' decisions to continue working there (Suwandi, 2019). Work discipline is a predictor of job satisfaction, organizational commitment, and turnover intentions.…”
Section: Introductionmentioning
confidence: 99%